2021
DOI: 10.1007/s00018-021-03974-9
|View full text |Cite|
|
Sign up to set email alerts
|

O2 permeability of lipid bilayers is low, but increases with membrane cholesterol

Abstract: Oxygen on its transport route from lung to tissue mitochondria has to cross several cell membranes. The permeability value of membranes for O2 (PO2), although of fundamental importance, is controversial. Previous studies by mostly indirect methods diverge between 0.6 and 125 cm/s. Here, we use a most direct approach by observing transmembrane O2 fluxes out of 100 nm liposomes at defined transmembrane O2 gradients in a stopped-flow system. Due to the small size of the liposomes intra- as well as extraliposomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…2017; Al‐Samir et al . 2021). Thus, one can speculate that the exchange of t‐tubular and extracellular fluids, driven by mechanical forces (McNary et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Al‐Samir et al . 2021). Thus, one can speculate that the exchange of t‐tubular and extracellular fluids, driven by mechanical forces (McNary et al .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, t-tubule membranes have high levels of cholesterol, which is reported to make membranes relatively impermeable to CO 2 , which should prevent significant leakage of CO 2 back into the cytosol. Interestingly, recent studies show that membrane permeability of O 2 increases as cholesterol increases (Dotson et al 2017;Al-Samir et al 2021). Thus, one can speculate that the exchange of t-tubular and extracellular fluids, driven by mechanical forces (McNary et al 2012) may have the potential to contribute not only to CO 2 disposal but also to O 2 delivery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to modulating the activity of specific membrane proteins, the high C/PL ratio of RBC may facilitate gas exchange, as the low oxygen permeability of phospholipid lipid bilayers increases with enrichment of membranes, with cholesterol reaching a plateau between 40 and 50% [2]. Itel et al [3] reported the first experiments showing that the permeability of cell membranes for CO 2 appears to be regulated by membrane cholesterol content and membrane protein gas channels over a wide range spanning 2 to 3 orders of magnitude.…”
Section: Role Of Membrane Cholesterol and Lipids In Rbc Physiologymentioning
confidence: 99%
“…In a similar vein, the permeability of dissolved gases, including oxygen , and carbon dioxide, is decreased by the presence of cholesterol. In some systems, however, the presence of cholesterol has been found to increase oxygen permeability by an order of magnitude …”
Section: Introductionmentioning
confidence: 99%
“…In some systems, however, the presence of cholesterol has been found to increase oxygen permeability by an order of magnitude. 50 In mixtures containing cholesterol that exhibit phase separation into liquid ordered (L o ) and liquid disordered (L d ) phases, the L o phase has lower water permeability. 29,51 However, the difference in water permeability between L o and L d is significantly lower than the difference between the permeability of gel and fluid phases of single-component lipid membranes.…”
mentioning
confidence: 99%